Kegiatan Memperkenalkan Proses Pembelajaran Matematika yang Menyenangkan Bagi Anak Sekolah Dasar - Fatima Retno Ningrum; Fikha Fauziah Al Amir; Fikri Puja Kesuma; Hazmi Hasbullah Hamzah; Hilwa Amatullah Afifah; Moch Aditya Pebriyadi; Dian Herdiana; Bobang Noorisnan Pelita (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The activity of actualizing the values ​​of Pancasila, the 2nd principle of Just and Civilized Humanity, aims to foster a spirit of learning in children because the learning method used is game-based so it is hoped that it will be easy for children to understand and not make children bored with learning so that a knowledgeable and civilized young generation is created. The crisis of the younger generation towards science and etiquette which can be seen from the lack of enthusiasm for learning in children and the ease with which children get bored when learning makes it difficult for children to understand the lessons given. Based on the problems above, we are students of UIN Sunan Gunung Djati Bandung, Department of Sharia Economic Law, Class B Group 6 in actualizing the values ​​of Pancasila to conduct tutoring activities for children. The various activities that we carry out begin with the opening and introduction of the activities that we will do for elementary school children in the area, delivering mathematics material to elementary school children in an interesting way so that children can understand it, making quizzes as a learning evaluation, holding various games so that children can learn and children are not bored, and give gifts so that children are happy and motivated in learning, and finally the closing of activities